Design and Fabrication of Layered Fiber-Reinforced Polymer Spring for Lightweight Vehicles - Dhia A. Alazawi; Mohammed Ismael Hameed (Iraqi Journal of Industrial Research)
Reducing the weight of a vehicle is a key aspect that affects its performance, driving economy and overall safety. The suspension system is one of the major components for weight saving in vehicles as it contributes to a considerable rate of the unsprung weight. The developing of hybrid materials technology can be employed for avoiding bulky leaf spring with identical load carrying ability and stiffness. This paper describes the design and experimental analysis of composite leaf spring made of woven glass fiber reinforced polymer (FRP). The main goal of this study is to investigate the load carrying capability, stiffness, and possibility for weight minimization in composite materials as a lightweight alternative to conventional metallic leaf springs. The effective geometric parameters have been designed for 1000 kg automobile mass. The finite element analysis has been used as a computer-based simulation technique for prediction spring thickness (h) related to safe displacement and induced stress due to the applied load. The numerical and experimental outcomes demonstrate the strength, durability, and fatigue performance of composite materials. Additionally, the proposed fabricated prototype demonstrates an 80% weight reduction compared to a steel multi leaf spring, confirming its suitability for lightweight and high efficiency applications.